Mutations in the SHANK2 synaptic scaffolding gene in autism spectrum disorder and mental retardation - Berkel, Simone; Marshall, Christian R.; Weiß, Birgit; Howe, Jennifer; Röth, Ralph; Moog, Ute; Endris, Volker; Roberts, Wendy; Szatmari, Peter; Pinto, Dalila; Bonin, Michael; Riess, Angelika; et al. (Nature genetics, 2010)
Using microarrays, we identified de novo copy number variations in the SHANK2 synaptic scaffolding gene in two unrelated individuals with autism-spectrum disorder (ASD) and mental retardation. DNA sequencing of SHANK2 in 396 individuals with ASD, 184 individuals with mental retardation and 659 unaffected individuals (controls) revealed additional variants that were specific to ASD and mental retardation cases, including a de novo nonsense mutation and seven rare inherited changes. Our findings further link common genes between ASD and intellectual disability.
Gesehen am 20.01.2023